Dual function of Src in the maintenance of adherens junctions during tracheal epithelial morphogenesis. - Shindo, M.; Wada, H.; Kaido, M.; Tateno, M.; Aigaki, T.; Tsuda, L.; Hayashi, S. (Development, 2008)
The downregulation of E-cadherin by Src promotes epithelial to mesenchymal transition and tumorigenesis. However, a simple loss of cell adhesion is not sufficient to explain the diverse developmental roles of Src and metastatic behavior of viral Src-transformed cells. Here, we studied the functions of endogenous and activated forms of Drosophila Src in the context of tracheal epithelial development, during which extensive remodeling of adherens junctions takes place. We show that Src42A is selectively activated in the adherens junctions of epithelia undergoing morphogenesis. Src42A and Src64B are required for tracheal development and to increase the rate of adherens junction turnover. The activation of Src42A caused opposing effects: it reduced the E-cadherin protein level but stimulated transcription of the E-cadherin gene through the activation of Armadillo and TCF. This TCF-dependent pathway was essential for the maintenance of E-cadherin expression and for tissue integrity under conditions of high Src activity. Our data suggest that the two opposing outcomes of Src activation on E-cadherin facilitate the efficient exchange of adherens junctions, demonstrating the key role of Src in the maintenance of epithelial integrity.